Economic implications of water efficiency measures I: assessment methodology and cost-effectiveness of micro-components. Issue 5 (28th May 2017) - Fidar, A. M.; Memon, F. A.; Butler, D.
Abstract: Economic efficiency has recently become one of the primary objectives of water management decisions. In particular, as vulnerability of freshwater systems has become evident and there is a trend for water supply managers to look towards water demand management, identifying the cost of such measures is becoming increasingly important. In England and Wales, Part G of the Building Regulations requires that water consumption of a new dwelling should not be more than 125 litres/capita.day. However, while compliance with this is determined by the water use characteristics of the installed micro-components (WCs, showers, basin taps, kitchen taps, baths, dishwashers and washing machines), the cost to consumers resulting from installing water efficient micro-components is not clear. This paper evaluates the potential economic implications of water saving micro-components, assessed from the consumers' perspective. A methodology has been developed and implemented to assess the cost-effectiveness of several types of water efficient micro-components. A range of cost assessment methods was applied, and critically reviewed comparing their outcomes. It was found that conventional cost assessment methods are unsuitable for identifying the least cost options to consumers. Of the applied methods, the modified annualised assessment method appears to be a relatively better option.